Rapid detection of K650E mutation in FGFR3 using uncultured amniocytes in a pregnancy affected with fetal cloverleaf skull, occipital pseudoencephalocele, ventriculomegaly, straight short femurs, and thanatophoric dysplasia type II - Chih-Ping Chen; Tung-Yao Chang; Ming-Huei Lin; Schu-Rern Chern; Jun-Wei Su; Wayseen Wang (Elsevier, 2013)
Objective: To present the ultrasound and molecular genetic diagnosis of thanatophoric dysplasia type II (TD2). Case Report: A 35-year-old, primigravid woman was referred to our institution for genetic counseling and amniocentesis at 19 weeks of gestation because of advanced maternal age and sonographic abnormalities in the fetus. The prenatal ultrasound showed short straight femurs, prominent forehead, narrow chest, skin edema, short limbs, and cloverleaf skull consistent with the diagnosis of TD2. Amniocentesis revealed a karyotype of 46,XX. DNA testing for the FGFR3 gene using uncultured amniocytes revealed a heterozygous c.1948A>G, AAG>GAG transversion leading to a p.Lys650Glu(K650E) mutation in the FGFR3 gene. A prenatal ultrasound at 21 weeks of gestation showed ventriculomegaly, cloverleaf skull, straight femurs, micromelia, narrow chest, and pseudoencephalocele with a bulging occipital bone mimicking encephalocele. The pregnancy was subsequently terminated, and a 480-g malformed fetus was delivered with macrocephaly, depressed nasal bridge, short upturned nasal tip, hypoplastic midface, frontal bossing, short digits, trident-shaped hands, short limbs, cloverleaf skull, narrow chest, brachydactyly, nuchal edema, and bulging occipital bone. Conclusion: A prenatal diagnosis of cloverleaf skull, short limbs, straight femurs, and occipital pseudoencephalocele should include a differential diagnosis of TD2. A molecular analysis of FGFR3 using uncultured amniocytes is useful for the rapid confirmation of TD2 at prenatal diagnosis.